Exploring experiences of practicum councelors' journey in supervision : a case study of undergraduate counceling programme using creative arts at International Islamic University Malaysia - Siti Kholijah binti Kassim (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Doing practicum is required in counseling training. Practicum counselor will meet client for the first time at a real setting. It is the beginning of one's professional journey. A qualitative study was conducted to explore the journey of a group practicum counselor. The experiences were shared using creative art during their weekly supervision. With the use of creative activities (drawing, play dough and play therapy tools), guided journal, reflective journal and focus group discussion, their challenges were explored and shared. The narratives from FGD and personal reflections or process journals were analyzed together with the products created. All thirty practicum counselors in the third year program of Bachelor of Education Guidance and Counseling who went through 7-week counseling practicum in the Klang Valley were involved in the study. Researcher used qualitative software, ATLAS.ti version 7. Throughout the process, the researcher generated and grouped the verbatim into categories, themes and subthemes and patterns reflecting on the research questions in a coding template. The data analysis processes required the researcher to be involved in description and interpretation of the data. For the journal, researcher used content analysis to get the gist and theme of the content. From the finding of the study, researcher divided the data into three phases. For the first phase ( pre- practicum), data revealed about the feeling of practicum counselor before going to the practicum site, challenges that they faced and sources of support they get at that time. For the second phase (during practicum) data represent for the seven week of practicum journey. Data revealed that practicum counselor have various kinds of challenges such as are interpersonal relationship, lack of counseling skills, contact hours, documentation of the counseling file and service. Although practicum counselor faced many challenges during the seven weeks of practicum, they adopted various kinds of coping strategies to deal with their personal and professional issues. Communicating with friends and university supervisor seem to be important source of information to cope better. The third phase (post –practicum) data revealed that practicum counselors expressed their challenges during practicum through the use of creative arts. The study manage to capture various feeling related to their experiences at different phases of the practicum journey (pre, during and post practicum). They found themselves to be more at ease and objective in sharing their issues based on their drawings and creations. They found that creative art and journal writing help them express their issues related to practicum and evaluate their coping reactions. The weekly meeting acted as a constant stress releaser to practicum counselor. The study also confirms the need for continuous support from supervisor and the platform to share their experiences during supervision. It will be interesting to find out how the practicum experience prepare them in fulfilling the bigger task of internship at the end of the programme as well as how relevant it is in their process of becoming a professional counselor